To solve the system of equations using the elimination method, we have:
-
\( 3x - 4y = -4 \) (Equation 1)
-
\( x + 3y = -10 \) (Equation 2)
First, let's manipulate Equation 2 to eliminate \( x \).
We can express \( x \) in terms of \( y \) from Equation 2:
\[ x = -10 - 3y \]
Now, substitute this expression for \( x \) into Equation 1:
\[ 3(-10 - 3y) - 4y = -4 \]
Expanding this gives:
\[ -30 - 9y - 4y = -4 \]
Combine like terms:
\[ -30 - 13y = -4 \]
Now, add 30 to both sides:
\[ -13y = 26 \]
Dividing both sides by -13 gives:
\[ y = -2 \]
Now, substitute \( y = -2 \) back into the equation we derived for \( x \):
\[ x = -10 - 3(-2) \]
Calculating \( x \):
\[ x = -10 + 6 = -4 \]
Thus, the solution is
\[ (x, y) = (-4, -2) \]
From the provided options, the correct answer is:
(−4,−2)